Malaria prevention in the age of climate change: A community survey in rural Senegal. - Andrew C L Sherman; C Andrew Aligne; Jesse D Matthews (PLoS ONE, 2025)
Background Malaria results in over 600,000 deaths per year, with 95 percent of all cases occurring in sub-Saharan Africa. Insecticide treated mosquito nets have long been proven to be the most effective prevention method to protect at-risk people from malaria. Temperature increases may now be changing sleeping habits and how people use available mosquito nets. Based on observations of increasing outdoor sleeping and fragility of the mosquito nets, this study evaluated a rural west African population to determine barriers to mosquito net use, including net fragility, heat and outdoor sleeping. Methods This study used a social ecological framework used by the Peace Corps to determine this community's barriers to malaria prevention. We practiced community-based participatory research by developing and implementing a survey in rural southeast Senegal. Local village health workers received special training to implement this survey. Observations of the mosquito nets and sleeping spaces were performed by surveyors. 164 households in 20 villages were surveyed from October to November of 2012. Results There was a 100% response rate, with 164 of the 164 selected households surveyed, representing 21% of this local population. For the 1806 family members, respondents assessed a total need of 1565 nets, implying that each individual in this area needs 0.86 nets (95% CI: 0.77-0.95). Survey responses gave rich, informative responses about mosquito net use. For example: 'If it's in the room set up properly under the mattress then it will be fine. But if it's outside with the beds that don't have mattresses, then it will deteriorate quickly.' The main reasons for not using an available net were heat and fragility of the nets. This population had very positive attitudes regarding mosquito nets and appreciated the work of local malaria educators. Conclusions In a rural Senegalese population with a high malaria burden, our survey indicated a need for 0.86 insecticide treated nets per person. This is 54% higher than the current WHO recommendation of 0.56 ITNs per person. Our findings suggest that there are not enough nets because routine village conditions lead to considerable net damage, and because the heat leads people to sleep outdoors, where they likely do not have mosquito nets. With global warming, we suspect this population will spend even more time sleeping outside, aggravating the current insufficiency. Further research should investigate optimal interventions to address this challenge, including nets designed for outside use and for higher durability.